Cesar Chavez holds a newborn child - Manuel Echavarria::::::photographer:::
Cesar Chavez holds a newborn child during one of his several visits to the Santa Maria Valley. UFW rallies and marches always included families and children as evident in this photo. Cesar Chávez sostiene un recién nacido en una de sus muchas visitas al Valle de Santa Maria. Las demostraciones siempre incluían la participación de familias con sus niños, como es evidente en esta fotografí